A comparison of the costs of in-office fluoride therapy versus salt fluoridation using - Reza Khani Jazani; Shabnam Seyedzadeh Sabounchi; Zahra Ghorbani; Hedieh Toutouni; Imaneh Asgari (Tehran University of Medical Sciences, 2013)
Background and Aims: Application of fluoride products is known as one of the most successful interventions to prevent dental caries. This study aimed to compare the costs of in-office fluoride therapy versus salt fluoridation in Iranian population.   Materials and Methods: In this study, the costs relating to the use of in-office fluoride therapy were analyzed using Activity Based Costing during 2011 from two perspectives. From the perspective of service provider, direct medical costs and indirect costs and from the view of service recipient, three parts: direct medical and non-medical costs and indirect costs, were considered. Costing for public consumption of salt fluoridation was estimated based on salt processing costs, including purchase, installation, monitoring, maintenance and repair of machinery, equipment, personnel expenses and cost of raw materials, used in this study.   Results: Costs relating to performing a single in-office fluoride therapy was estimated to be 245,032 Rials from the perspective of service providers, and 239,600 Rials from the patient view. Estimated total cost to produce fluoridated salt for a unit of 10 million populations, was calculated to be 35 billion and 940 million Rials or 3, 594 Rials per person per year.   Conclusion: It was concluded that per-capita costs of community based salt fluoridation was far less than in-office fluoride therapy. Salt fluoridation could be advised to be an affordable way to prevent dental caries in Iranian population.